2011
DOI: 10.1089/dna.2011.1384
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Tetherin Restricts Vesicular Stomatitis Virus Release in Neurons

Abstract: Tetherin, a recently identified interferon (IFN)-inducible, type 2 transmembrane protein, has been shown to be a cellular antiviral restriction factor that retains newly formed virions in infected cells. Thus, tetherin plays an important role in the innate cell-autonomous immune response. The aim of this study was to examine the antiviral activities of tetherin in vesicular stomatitis virus infections of murine neuronal cells. Both IFN-b and IFN-g induce the expression of tetherin mRNA and protein. Tetherin kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Tetherin expression was also evaluated in the TG by PCR at day 5 pi (Supplemental Figure 1b) in light of evidence showing tetherin expression in neurons 30,31 and the enhanced trafficking of HSV-1 from the cornea to the TG in STING −/− and CD118 −/− mice observed herein (Supplemental Figure 1a). Though STING is required for tetherin expression in the corneal epithelium (Figure 4c, Supplemental Movie 1), tetherin is upregulated in the TG of STING −/− mice similarly to WT at an approximate 8-fold increase over UI yet conspicuously absent in CD118 −/− TG at day 5 pi (Supplemental Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Tetherin expression was also evaluated in the TG by PCR at day 5 pi (Supplemental Figure 1b) in light of evidence showing tetherin expression in neurons 30,31 and the enhanced trafficking of HSV-1 from the cornea to the TG in STING −/− and CD118 −/− mice observed herein (Supplemental Figure 1a). Though STING is required for tetherin expression in the corneal epithelium (Figure 4c, Supplemental Movie 1), tetherin is upregulated in the TG of STING −/− mice similarly to WT at an approximate 8-fold increase over UI yet conspicuously absent in CD118 −/− TG at day 5 pi (Supplemental Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…were similar in spleens and salivary glands on days 3 and 14 p.i., respectively (Figure 2B). It has been reported that BST2 inhibits the release of VSV from infected cells (19, 20) so we next infected mice i.v. with VSV-OVA.…”
Section: Resultsmentioning
confidence: 99%
“…BST2 is an ISG encoded type 2 transmembrane protein that functions as an antiviral restriction factor. Importantly, recent studies have indicated that BST2 inhibits VSV release by neuroblastoma cells (Sarojini et al, 2011). In addition, the IFN-induced with tetratricopeptide repeats 2 (Ifit2) gene has been implicated in VSV neurotropism as Ifit2 deficient animals show increased susceptibility to VSV infection delivered via the i.n.…”
Section: Neurotropism Of Vsvmentioning
confidence: 99%